Functional Heterogeneity of NAPDH Oxidase-Mediated Contractions to Endothelin with Vascular Aging - Meyer, Matthias R. (2013)
AIMS: Aging, a physiological process and main risk factor for cardiovascular and renal diseases, is associated with endothelial cell dysfunction partly resulting from NADPH oxidase-dependent oxidative stress. Because increased formation of endothelium-derived endothelin-1 (ET-1) may contribute to vascular aging, we studied the role of NADPH oxidase function in age-dependent contractions to ET-1. MAIN METHODS: Renal arteries and abdominal aortas from young and old C57BL6 mice (4 and 24 months of age) were prepared for isometric force measurements. Contractions to ET-1 (0.1–100 nmol/L) were determined in the presence and absence of the NADPH oxidase-selective inhibitor gp9Ids-tat (3 µmol/L). To exclude age-dependent differential effects of NO bioactivity between vascular beds, all experiments were conducted in the presence of the NO synthase inhibitor L-NAME (300 µmol/L). KEY FINDINGS: In young animals, ET-1-induced contractions were 6-fold stronger in the renal artery than in the aorta (p<0.001); inhibition of NADPH oxidase by gp9 Ids-tat reduced responses to ET-1 by 50% and 72% in the renal artery and aorta, respectively (p<0.05). Aging had no effect on NADPH oxidase-dependent and -independent contractions to ET-1 in the renal artery. In contrast, contractions to ET-1 were markedly reduced in the aged aorta (5-fold, p<0.01 vs. young) and became insensitive to gp9Ids-tat. SIGNIFICANCE: The results suggest an age-dependent heterogeneity of NADPH oxidase-mediated vascular contractions to ET-1, demonstrating an inherent resistance to functional changes in the renal artery but not in the aorta with aging. Thus, local activity of NADPH oxidase differentially modulates responses to ET-1 with aging in distinct vascular beds.